2021
DOI: 10.1021/acsearthspacechem.1c00204
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Oxidants and Temperature in the Formation of Biogenic Organosulfates and Nitrooxy Organosulfates

Abstract: Biogenic secondary organic aerosol (BSOA) makes up a significant proportion of organic aerosol, and its formation chemistry, composition, and physical properties can be influenced by anthropogenic emissions, especially in urban areas. Organosulfates (OSs) are an important class of tracers for BSOA and have been well-studied over the past decade, although detailed ambient studies of diurnal variations are still lacking. In this study, fine particulate matter samples were collected eight times a day across summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 85 publications
10
28
0
Order By: Relevance
“…Figure 2b shows the annual variations of the sum relative abundance of the above five OSs groups to the total OrgSs abundance, with annual average proportions of 3.8±1.9%, 23±6.7%, 3.6±0.5%, 6.1±1.4% and 27±2.3% for isoprene-derived, monoterpene-derived, other BVOCs-derived, anthropogenic VOCs-derived OSs and multiple-source-derived OSs, respectively. The high contribution of known terpene-derived OSs to the total OrgSs intensity in GZ is consistent with previous observations of the dominance of terpene-derived OSs in GZ (Wang et al, 2017b;He et al, 2014;Bryant et al, 2021). Several acid-catalyzed chemistry of BVOCs-derived oxidation products (Hettiyadura et al, 2019;Bruggemann et al, 2020).…”
Section: Potential Precursor Appointment Of Orgss With Previous Knowledgesupporting
confidence: 91%
See 3 more Smart Citations
“…Figure 2b shows the annual variations of the sum relative abundance of the above five OSs groups to the total OrgSs abundance, with annual average proportions of 3.8±1.9%, 23±6.7%, 3.6±0.5%, 6.1±1.4% and 27±2.3% for isoprene-derived, monoterpene-derived, other BVOCs-derived, anthropogenic VOCs-derived OSs and multiple-source-derived OSs, respectively. The high contribution of known terpene-derived OSs to the total OrgSs intensity in GZ is consistent with previous observations of the dominance of terpene-derived OSs in GZ (Wang et al, 2017b;He et al, 2014;Bryant et al, 2021). Several acid-catalyzed chemistry of BVOCs-derived oxidation products (Hettiyadura et al, 2019;Bruggemann et al, 2020).…”
Section: Potential Precursor Appointment Of Orgss With Previous Knowledgesupporting
confidence: 91%
“…Moreover, directly assessing relationships between individual compounds and LWC, NO3 − , NH4 + suggested that the increase of their concentrations would promote the formation of CHONS species, as 72%, 65% and 75% of the OrgSs that have positive correlations (p adjust with "fdr") with the LWC, NO3 − , NH4 + , are CHONS species (Table S13), respectively, further supports the OrgSs formation via aqueous-phase chemistry in Guangzhou influenced by LWC, such as NO3-initiated oxidation, acidcatalyzed epoxide pathways (Wang et al, 2020;Xu et al, 2021b). Recently, Bryant et al (2021) reported that oxidants and temperature are important factors that affect OSs formation in Guangzhou, and high-NOx pathways became more important in the winter when usually suffering high anthropogenic emissions, while low-NO formation pathways were dominant in the summer. The observed opposite influence of OH radicals and inorganic species on OrgSs distributions also suggested the existence of OrgSs formation from heterogeneous OH radical oxidation when there was less anthropogenic emission Lam et al, 2019).…”
Section: Possible Formation Pathways Of Orgss and The Influencing Factorsmentioning
confidence: 66%
See 2 more Smart Citations
“…Globally, isoprene is predominately emitted from biogenic sources, but anthropogenic sources become increasingly important in urban areas especially at night (Borbon et al, 2001;Hsieh et al, 2017;Khan et al, 2018a;Mishra and Sinha, 5 al., 2013;Surratt et al, 2008a) were searched for in an afternoon and a night-time filter sample extract analysis using the Xcalibur software. Further details can be found in Bryant et al, 2021 and the SI. Isoprene and monoterpene markers were quantified using the method in Bryant et al, 2021. Overall uncertainties associated with calibrations, proxy standards and matrix effects were estimated.…”
Section: Introductionmentioning
confidence: 99%